Implikasi Teologis Pelayan Tahbisan Perempuan di Gereja Pantekosta Pusat Surabaya (GPPS) Gatotan Surabaya: The Theological Implications of Female Ordination in the Pentecostal Church of Surabaya Central (GPPS) Gatotan Surabaya - Yedida Mauk; Amran Simangunsong; Antonius Missa (Journal of Religious and Socio-Cultural, 2025)
The Church is rooted in life and proclamation through the events of Jesus' death, resurrection, and the sending of the Holy Spirit to the disciples. The sending of the disciples after Pentecost established various ministries within the church, such as prophets, apostles, evangelists, pastors, and teachers. These ministries are integrated into the role of the pastor, also referred to as the ordained minister. Ordained ministers are chosen by the church or synod if they have received the sacrament of Holy Communion, been baptized, and meet the church's requirements. Ordained ministry is open to both genders, men and women. However, churches have often adopted a patriarchal view, considering men as the suitable candidates for ordained ministry due to their role as the first creation of God, with authority and a direct reflection of God's image and glory. This perspective was previously upheld by the Pentecostal Church of Surabaya Central (GPPS) Gatotan, where patriarchy was prioritized, making it difficult for women to serve as ordained ministers. Feminist theology critiques this patriarchal dominance, particularly in the context of ordained ministry within the church, focusing on GPPS Gatotan. Through a hermeneutic analysis of official church documents, GPPS Gatotan recognized the importance of the role of female ordained ministers as part of the inclusive message of the Gospel. This research contributes to understanding how feminist theology can challenge patriarchal structures and promote gender inclusivity in church leadership, especially within Pentecostal contexts. Gereja berakar dari hidup dan pewartaan melalui peristiwa kematian Yesus, kebangkitan-Nya, dan pengutusan Roh Kudus kepada para murid. Pengutusan para murid setelah Pentakosta membentuk berbagai jawatan dalam gereja, seperti nabi, rasul, penginjil, gembala, dan pengajar. Kelima jawatan ini termasuk dalam jabatan gereja yang disebut dengan Pelayan Tahbisan. Pelayan Tahbisan dipilih oleh gereja atau Sinode Gereja setelah memenuhi syarat sakramen Perjamuan Kudus, baptisan, dan persyaratan gereja lainnya. Jabatan ini terbuka untuk kedua gender, baik laki-laki maupun perempuan. Namun, gereja sering kali memandang jabatan ini melalui kacamata patriarki, dengan anggapan bahwa laki-laki lebih layak karena dianggap sebagai manusia pertama yang diciptakan oleh Allah, memiliki wibawa, dan menggambarkan kemuliaan Allah secara langsung. Pandangan ini diterapkan di Gereja Pantekosta Pusat Surabaya (GPPS) Gatotan, yang memprioritaskan patriarki, sehingga peran perempuan sebagai Pelayan Tahbisan sulit diterima. Teologi feminis hadir untuk mengkritisi dominasi patriarki dalam pelayanan tahbisan di gereja, khususnya di GPPS Gatotan. Melalui analisis hermeneutik terhadap dokumen resmi gereja, GPPS Gatotan menyadari pentingnya peran pelayan tahbisan perempuan sebagai bagian dari pesan Injil yang inklusif. Penelitian ini berkontribusi dalam memahami bagaimana teologi feminis dapat menantang struktur patriarki dan mendorong inklusivitas gender dalam kepemimpinan gereja, khususnya dalam konteks gereja Pantekosta.